The complete Neat stuff - Bagge, Peter 1957- (Fantagraphics Books, 2016)
"Neat Stuff is Bagge’s one-man humor anthology that ran from 1985 to 1989 for fifteen issues and introduced the world to Girly Girl & Chuckie-Boy, the reactionary talk radio host Studs Kirby, the hulking misfit Junior, suburbanites Chet and Bunny Leeway, the Goon on the Moon, lounge lizard Zoove Groover, and Bagge’s signature creations, The Bradleys. Black & white with 32 pages of color"--Amazon.com
The definitive collection of all fifteen issues of Peter Bagge's legendary comic book series, with new artwork and annotations by the author
Keywords: Bagge, Peter -- 1957-; Comic books, strips, etc; Humorous comics; Graphic novels; Comics (Graphic works) / United States; Comic